A polynomial based dynamic expansion and data consistency assessment and modification for cylindrical shell structures. (1st June 2021) - Chen, Yuanchang; Avitabile, Peter; Page, Christopher; Dodson, Jacob
Highlights: Developed a polynomial based dynamic expansion for cylindrical shell structure. Evaluated the consistency of a set of measurements by using a modified Data. Consistency Assessment Function (DCAF). Identified the inconsistent data and modified them to be consistent. Validated the technique by experimental data in either air or water. Abstract: A designated set of shape functions are created for cylindrical shell structures. The 1D Chebyshev polynomial is applied along the axial direction and the 1D harmonic basis along the circumferential direction. A 2D orthogonal space is formed on the cylindrical domain by combining the above two 1D bases and is used to develop the expansion function. A finite element model is not required for the expansion technique, nor are the boundary conditions or external forcing functions. Using these generated shape functions, the dynamic time response at some points on cylindrical shells structure can be expanded to obtain the information at a larger number of points. Only the measurement data, geometry, and coordinates of measured points are needed. The developed polynomial expansion technique is also extended to a Data Consistency Assessment Function (DCAF), which can assess the consistency of the data set and identify the inconsistent points. The inconsistent points can also be modified by using the polynomial expansion method. A cylindrical shell structure in either air or water medium is used to experimentally demonstrate the use of the developed shape functions for polynomial expansion and data consistency assessment and modification.